125: DETERMINANTS OF MATERNAL HEALTH CARE UTILIZATION AMONG BENEFICIARIES OF CONDITIONAL CASH INCENTIVES: EVIDENCE FROM A POST-DISASTER SETTING. (24th August 2015) - Valera, Marian Theresia D; Silfverberg, Denise Valerie R
Abstract : Background: This paper examines maternal health care (MHC) utilization among the beneficiaries of a recovery assistance program implemented by the Zuellig Family Foundation in partnership with the United States Philippine Society in select Philippine municipalities devastated by Typhoon Haiyan. The program aims to improve the utilization of maternal health care services among poor women by providing temporary support in the form of cash incentives received after the availment of prenatal care, facility-based delivery, and postnatal care services. Objectives: The study aims to explore the relationship between the utilization of MHC services in post-disaster settings and socio-demographic, demand-side, and supply-side factors. Methods: A mixed-methods approach was employed, with data derived from a sample of program beneficiaries. The probability of facility based deliveries (FBD) and of mothers having complete and timely prenatal care (PNC) visits were determined using probit analysis. Marginal effects for selected socio-demographic, demand-side and supply-side variables were estimated to identify the determinants of maternal health care utilization. Result: The key findings suggest that mother's education, age at first pregnancy, and availment of complete and timely PNC visits are significant determinants for the utilization of FBD. Moreover, the findings reveal that the probability of mothers having complete and timely PNC visits are associated with the provision of urinalysis services in health centers, amount of transportation costs incurred, child's birth order, and mother's age at first pregnancy. Conclusion: The results suggest that, aside from socio-demographic factors, the demand for maternal health care is also an important driver for facility-based delivery. This finding is supported by qualitative responses on beliefs and perceptions regarding MHC services. The significance of supply-side factors especially in a post-disaster setting, such as the availability and accessibility of health care services, is pronounced for prenatal care utilization. These findings provide evidence of the importance of supply and demand-side factors in influencing MHC service utilization at different stages in a post-disaster setting.